How sweet the sound my life with God and gospel - Houston, Cissy 1933-2024 (Doubleday, 1998)
Cissy is a Grammy-winning gospel singer and the proud mother of pop-music sensation Whitney Houston. She has starred in Off-Broadway shows and shared the screen with her daughter. But Cissy Houston's life is really about finding meaning, direction, and love; it is about being a woman of high moral principles and integrity in a world where both seem to be lacking; it is about being a wife, a mother, and a sister in the tug-of-war between family and a career that took her all around the world. Born Cissy Drinkard in a tough Newark, New Jersey, neighborhood in 1933, she was the youngest of eight children. With her father's talent and love of four-part gospel, she started singing at a young age and never stopped, no matter what happened in her life.--From publisher description.
Keywords: Houston, Cissy; Houston, Cissy -- 1933-2024; African American singers -- Biography; Gospel musicians -- United States -- Biography; Autobiografie; USA; Biografie